Memes everywhere: The effect of social media memes on consumers' attitude towards brands and their purchase intention - Burak Pilavcioglu; Alexander Hodeck; Niels Nagel; Marcus Simon; Timo Zimmermann; Klaus Mühlbäck (PraxisWISSEN Marketing, 2023)
With the literally ever-lasting relevance of social media and the constant development of online communication, memes are more and more gaining popularity. So far there is only little scientific research on the advertising effectiveness of memes. This study aims to close this knowledge gap and tests, if memes have a positive effect on consumers' attitude towards the advertisement, towards the brand and on their purchase intention. Results of an empirical study indicate that ads with memes, despite being perceived as humorous, did not perform significantly better than control group ads. – – Mit der ungebrochenen Relevanz sozialer Medien und der ständigen Weiterentwicklung der Online-Kommunikation gewinnen Memes zunehmend an Popularität. Es gibt es nur wenige wissenschaftliche Untersuchungen zur Werbewirksamkeit von Memes. Die vorliegende Studie soll diese Wissenslücke schließen. Sie prüft, ob Memes einen positiven Effekt auf die Einstellung der Konsumentinnen und Konsumenten zur Werbung, zur Marke und auf die Kaufabsicht haben. Die Ergebnisse einer empirischen Studie zeigen, dass Anzeigen mit Memes, auch wenn sie als humorvoll wahrgenommen werden, nicht signifikant besser abschneiden als Anzeigen der Kontrollgruppe.
Keywords: 650; Memes; humor; social media marketing; attitude; advertisement; brand; purchase intention; brand recall